2001
DOI: 10.1039/b107037a
|View full text |Cite
|
Sign up to set email alerts
|

In situ STM imaging of surface dissolution and rearrangement of a Pt–Fe alloy electrocatalyst in electrolyte solution

Abstract: The formation of a Pt skin layer with predominantly (111)-oriented facets induced by dissolution of Fe atoms in a Pt-Fe alloy for fuel cell applications is investigated for the first time by using in situ electrochemical STM in 0.1 M HClO4 solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 13 publications
1
104
0
Order By: Relevance
“…27,41,74,[89][90][91] Electrochemical scanning tunnelling microscopy (EC-STM) experiments have shown that on a leached PtFe thin film, ordered (111) facets form on the catalyst surface. 92 The vacuum annealed structure was denoted by Stamenkovic et al as a ''Pt-skin'' surface. 89 The Pt overlayer is typically 1 monolayer thick.…”
Section: How To Reach the Peak Of The Volcano?mentioning
confidence: 99%
“…27,41,74,[89][90][91] Electrochemical scanning tunnelling microscopy (EC-STM) experiments have shown that on a leached PtFe thin film, ordered (111) facets form on the catalyst surface. 92 The vacuum annealed structure was denoted by Stamenkovic et al as a ''Pt-skin'' surface. 89 The Pt overlayer is typically 1 monolayer thick.…”
Section: How To Reach the Peak Of The Volcano?mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] For example, the values of j k for Pt-Co alloys showed a maximum at the atomic ratio of Pt/Co = 3. 4,5,14 It has been reported that the electronic structure of the Pt skin layer formed on Pt-M alloys could change with the composition of the underlying alloy, reaching a maximum at the optimum alloy composition or alloying metal species M. 24,[30][31][32] Because the surface is not perfectly covered with uniform Pt skin layer, j k often decreases appreciably by dealloying of M during the operation of PEFCs or electrochemical measurements in acidic electrolyte solutions, particularly at higher temperatures. 14,33 Here, we focus on the influence of crystal structure (ordered and disordered structures) of Pt 3 Co alloy nanoparticles on the ORR activity and durability.…”
mentioning
confidence: 99%
“…This will be discussed in more detail in Section 3.1.1. [42][43][44][45][46][47][48][49] ard hydrogen electrode by a H 2 SO 4 as used as shown in Fig. 1.…”
Section: Pemfc Cell Reversal Descriptionmentioning
confidence: 99%